Investigations on the effect of surface coatings on the weldment properties on chromium manganese stainless steel gas tungsten arc welded plates. (2021) - Sudhakaran, R.; Sivasakthivel, P.S.; Subramanian, M.
Abstract: This paper reports the enhancements for the effects of specific fluxes such as Tungsten Carbide and Chromium Oxide on the weldment properties such as micro hardness, weld bead geometry and tensile strength obtained with Gas Tungsten Arc Welding Process (GTAW) applied to 6 mm thick Chromium Manganese stainless steel plates. The significant expense of Nickel has made Chromium Manganese stainless steel as an option for conventional 300 arrangement stainless steel. The two fluxes tungsten carbide and chromium oxide were utilized in powdered structure. The tensile test, micro hardness test and corrosion resistance test was conducted to reveal the effect of fluxes on the weldment properties. Results of tensile shows that considerable enhancement in tensile strength and elongation of about 20% increase in case of Chromium Oxide coated samples and 10% increase in case of Tungsten Carbide samples when compared to uncoated specimen. In case of microhardness, 10% increase is exhibited for coated samples compared with uncoated samples. The corrosion rate of coated samples found to be highly resistant for coated samples, which sums to be 300% more than that of uncoated samples. The effect of corrosion rate on the specimens was seen by conducting SEM analysis after the corrosion test. The SEM analysis uncovered that the coating covers the limits encompassing the inclusions and encloses dendrites which reduce the pitting corrosion of the parent metal.